Pengaruh Media Permainan Monopoli Terhadap Kemampuan Berpikir Historis Siswa Kelas XI MIPA 8 SMA Negeri 1 Tasikmalaya - Ulfah Khoerun Nisa; Oka Agus Kurniawan Shavab; Iyus Jayusman (Jurnal Pendidikan Sejarah, 2020)
The purpose of this thesis writing is to find out the influence of monopoly game media on students' historical thinking ability on history subjects in the XI MIPA 8 class of SMA Negeri 1 Tasikmalaya even semester semester 2019/ 2020. The method used in this research is quasi-experimental with a quantitative approach. The design used is nonequivalent control group design. The population in this study were all students of class XI MIPA of SMA Negeri 1 Tasikmalaya which were divided into 9 classes. The sample in this study was determined using a purposive sample technique, namely class XI MIPA 8 as an experimental class and XI MIPA 9 as a control class. Data collected through observation and tests. The instruments used are observation guidelines and items in the form of descriptions with indicators of historical thinking. the number of description questions used is 7 items after validity testing. Data analysis techniques were performed using SPSS software version 25.0. The results showed that the use of monopoly games in class XI MIPA 8 had an effect on increasing the ability to think historically. This is based on the results of data processing which shows that the value of t count> t table (6.248> 2,000) or Sig (2-Tailed) value of 0.00 <0.05 so that Ho is rejected and Ha is accepted. The effectiveness of the monopoly game as a medium of learning in history subjects is stated to be quite effective in improving the historical thinking ability of students of class XI MIPA 8 of SMA Negeri 1 Tasikmalaya semester even academic year 2019/ 2020.